2020
DOI: 10.3390/electronics9010063
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Active Components Count Electronically Adjustable Fractional-Order Controllers: Two Design Examples

Abstract: This paper deals with fractional-order controller implementations, which can be constructed by electronically controlled building blocks fully integrated on a single chip. The proposed DC motor controller structure offers 50% reduction of the active components count, compared to the corresponding already published counterpart. The proposed liquid level of the two-interacting-tank controller scheme is the first one in the literature offering the aforementioned features. Simulation results, based on the 0.35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Considering that ω pade = ω c = 10rad/s, the resulting 5th-order transfer function of the controller is given by (17), with the values of coefficients being summarized in Table 2. The gain and phase frequency responses obtained from (17), along with theoretically predicted ones given by dashes, are depicted in the plots of Figure 1, where the efficiency of the Padé approximation is readily obtained.…”
Section: Approximation Of Controller Transfer Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that ω pade = ω c = 10rad/s, the resulting 5th-order transfer function of the controller is given by (17), with the values of coefficients being summarized in Table 2. The gain and phase frequency responses obtained from (17), along with theoretically predicted ones given by dashes, are depicted in the plots of Figure 1, where the efficiency of the Padé approximation is readily obtained.…”
Section: Approximation Of Controller Transfer Functionmentioning
confidence: 99%
“…The gain and phase frequency responses obtained from (17), along with theoretically predicted ones given by dashes, are depicted in the plots of Figure 1, where the efficiency of the Padé approximation is readily obtained. The rational integer-order transfer function in (17) can be implemented by following well-known filter design techniques, including series (e.g., multifeedback schemes) as well the parallel connection of fundamental filter functions. The presented concept is general, in the sense that it is independent of the parameters of the FO-[PD] controller, and from the type of the employed plant, it offers versatility from an implementation point of view.…”
Section: Approximation Of Controller Transfer Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several works on the analog circuit realization of the FOPID controller reported in the literature, using analog blocks like Operational Transconductance Amplifier (OTA) [32], [33], CCII [34], Voltage Differencing Current Conveyor (VDCC) [35]. Most of these circuits suffer from drawbacks, such as a high number of active/ passive elements [32], [33], and lack of electronic tunability [34].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that fractional-order controllers result in effectively better control proficiency in comparison with the integer-order counterpart [13][14][15]. However, this control approach has rarely applied on PV/battery systems, and only some simple fractional-order controllers with no stability guarantee have been developed.…”
Section: Introductionmentioning
confidence: 99%